Secure Data Management Third VLDB Workshop, SDM 2006, Seoul, Korea, September 10-11, 2006, Proceedings - Jonker, Willem; Petkovic, Milan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Recent developments in computer, communication, and information techno- gies, along with increasingly interconnected networks and mobility have est- lished new emerging technologies, such as ubiquitous computing and ambient intelligence, as a very important and unavoidablepartof everydaylife. However, this development has greatly in?uenced people’s security concerns. As data is accessible anytime from anywhere, according to these new concepts, it becomes much easier to get unauthorized data access. As another consequence, the use of new technologies has brought some privacy concerns. It becomes simpler to collect, store, and search personal information and endanger people’s privacy. Therefore, research in the area of secure data management is of growing imp- tance, attracting the attention of both the data management and security - search communities. The interesting problems range from traditional ones such asaccesscontrol(withallvariations,likerole-basedand/orcontext-aware),da- base security, operations on encrypted data, and privacy preserving data mining to cryptographic protocols. The call for papers attracted 33 papers both from universities and ind- try. The program committee selected 13 research papers for presentation at the workshop. These papers are also collected in this volume, which we hope will serve you as useful research and reference material.
Privacy Protection -- Indistinguishability: The Other Aspect of Privacy -- Sovereign Information Sharing Among Malicious Partners -- Temporal Context Lie Detection and Generation -- Secure Anonymization for Incremental Datasets -- Privacy Preserving Data Management -- Difference Set Attacks on Conjunctive Keyword Search Schemes -- Off-Line Keyword Guessing Attacks on Recent Keyword Search Schemes over Encrypted Data -- Privacy Preserving BIRCH Algorithm for Clustering over Vertically Partitioned Databases -- Access Control -- Conflict of Interest in the Administrative Role Graph Model -- Two Phase Filtering for XML Access Control -- Hybrid Authorizations and Conflict Resolution -- Database Security -- Analysis of a Database and Index Encryption Scheme – Problems and Fixes -- Information Disclosure by XPath Queries -- SPIDER: An Autonomic Computing Approach to Database Security Management.
Keywords: Data structures (Computer science).; Database management; Information storage and retrieval; Computer communication systems; Data encryption (Computer science).; Operating systems (Computers).; Data Structures and Information Theory; Database Management; Information Storage and Retrieval; Computer Communication Networks; Cryptology; Operating Systems